The non-receptor tyrosine kinase Tec controls assembly and activity of the noncanonical caspase-8 inflammasome. - Florian Zwolanek; Michael Riedelberger; Valentina Stolz; Sabrina Jenull; Fabian Istel; Afitap Derya Köprülü; Wilfried Ellmeier; Karl Kuchler (PLoS Pathogens)
Tec family kinases are intracellular non-receptor tyrosine kinases implicated in numerous functions, including T cell and B cell regulation. However, a role in microbial pathogenesis has not been described. Here, we identified Tec kinase as a novel key mediator of the inflammatory immune response in macrophages invaded by the human fungal pathogen C. albicans. Tec is required for both activation and assembly of the noncanonical caspase-8, but not of the caspase-1 inflammasome, during infections with fungal but not bacterial pathogens, triggering the antifungal response through IL-1β. Furthermore, we identify dectin-1 as the pathogen recognition receptor being required for Syk-dependent Tec activation. Hence, Tec is a novel innate-specific inflammatory kinase, whose genetic ablation or inhibition by small molecule drugs strongly protects mice from fungal sepsis. These data demonstrate a therapeutic potential for Tec kinase inhibition to combat invasive microbial infections by attenuating the host inflammatory response.